Synthesis and Spectroscopic Studies of Substituted Three Different vic-Dioximes with New Binuclear Zn(II) Complexes - Duman, Sibel; Sekerci, Memet (Asian Journal of Chemistry, 2010)
The synthesis, spectroscopic properties of Zn(II) metal complexes with three novel substituted amino vic-dioxime ligands, N,N'-[2,2'{ethane-1,2-di-yl-bis(oxy)bis(2,1-phenylene) bis(N'-hydrox y)-2(hydroxylmino)acetanndamide] ((LH4)-H-1), N.N'-[43.3'-{ethane-1,2-di-ylbis(oxy)bis(3,1-phenylene))bis(N'-hydroxy)-2-(hydroxyimino) acetamidamidel ((LH4)-H-2) and N,N.-14,4'-{ethane-1,2-di-yl-bis(oxy)bis(4,1phenylene))/ns(N'-hydmxy)-2-(hydroxyimino) acetamidamidel ((LH4)-H-1), prepared 1.2-bis(o-aminophenoxy)ethane. 1,2-bis(m-aminophenoxy) ethane and 1.2-bis(p-aminophenoxy)ethane with antichloroglyoxime are reported. The structure of these amino vic-dioximes have been as the ant form according to 'H NMR and FT-IR data. The metal to ligand ratio of Zn(II) complexes are found to be 2.2. The Zn(II) complexes of these ligands are proposed to be tetrahedral or octahedral The structures of ligands and their complexes are proposed from elemental analyses, FT-IR. UV vis. 'H NMR, magnetic susceptibility measurements and TCIA-DTA analysis
Keywords: Synthesis; Amino vic-dioxime; Zn(II) complexes